2021
DOI: 10.1186/s40168-021-01100-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota long-term dynamics and prediction of acute graft-versus-host disease in pediatric allogeneic stem cell transplantation

Abstract: Background Patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT) exhibit changes in their gut microbiota and are experiencing a range of complications, including acute graft-versus-host disease (aGvHD). It is unknown if, when, and under which conditions a re-establishment of microbial and immunological homeostasis occurs. It is also unclear whether microbiota long-term dynamics occur at other body sites than the gut such as the mouth or nose. Moreover, it is not known wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 64 publications
(65 reference statements)
3
68
1
Order By: Relevance
“…At that time, the oral microbiome is most different from pre-SCT conditions. The present study, as well as our previous study in autoSCT recipients and the study of Ingham et al, showed that the oral microbiome is resilient as it returns to pre-SCT levels three months after SCT, remaining relatively stable in the first 12 to 18 months following SCT [10,15].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…At that time, the oral microbiome is most different from pre-SCT conditions. The present study, as well as our previous study in autoSCT recipients and the study of Ingham et al, showed that the oral microbiome is resilient as it returns to pre-SCT levels three months after SCT, remaining relatively stable in the first 12 to 18 months following SCT [10,15].…”
Section: Discussionsupporting
confidence: 82%
“…The decrease in oral bacterial diversity after SCT has been described by our group after autologous SCT [10] and by others in both adults and children in alloSCT and autoSCT patients [9,[14][15][16][31][32][33]. Most studies described a significant change in microbial composition directly after SCT.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…A potential role in the development of Chron's disease has also been suggested for lecithins 95 – 97 , and an experimental study among humans suggests a link between lecithins and coronary artery disease through the production of a proatherosclerotic metabolite, trimethylamine-N-oxide (TMAO) 94 . In a study on ex-vivo models of human microbiota, 20 emulsifiers were tested and a large majority (including carboxymethylcellulose, polysorbate 80, carrageenans, guar/xanthan gums, lecithins), were able to directly modify the gut microbiota in a way that could promote gut inflammation 23 . Carrageenans have been linked to fasting hyperglycemia and exacerbated glucose intolerance and hyperlipidemia without effect on weight in mice 31 .…”
Section: Discussionmentioning
confidence: 99%